SISTEM INFORMASI PEMETAAN DATA ALUMNI DAN LOWONGAN KERJA: Studi Kasus : SMK Nurul Islam Cianjur - Uro Abdurohim; Maurien Desiana Effendi; Linda Apriyanti (LPPM STMIK Bandung, 2020)
Today, the development of technology and information is rapidly advancing in various aspects of life, one of which is in the academic field, from elementary schools to universities. Nowadays, schools are increasingly using information technology in their academic management, making it easier to handle related data. Vocational schools, or SMKs, provide secondary education with the role of preparing students to enter the workforce. SMKs have an institution called the Special Labor Exchange (BKK), which serves as a placement service for workers in both secondary and higher education units. The Special Labor Exchange acts as a bridge between SMKs and the industrial world. SMK Nurul Islam Cianjur is a private school in the form of a foundation. This school also offers a Special Labor Exchange (BKK) program primarily for its alumni but is also available to students from other schools.